PENDAMPINGAN DESAIN MASTER PLAN WISATA MANGROVE KALI MIRENG DESA MANYAR SIDOMUKTI KABUPATEN GRESIK - Sholichin, Moh; Tri Budi Prayogo; Aris Subagyo; Wike Agustin Prima Dania; Onni Meirezaldi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The potential of Mangrove plants in Manyarsidomukti Village is an important thing that supports the continuity of environmental sustainability aspects and is very open to being managed to improve the village economy through tourism development. The presence of mangrove plants in Manyarsidomukti village is increasingly narrowing from year to year due to pressure for the development of industrial areas around it. The condition of the community resources in Manyarsidomukti Village is limited, where most of the residents are fishermen and traders with the educational level of most of the Senior High School (SMA). Therefore, the location of Manyarsidokukti Village is the right choice for community service activities by the Doktor Serving (DM) team to carry out assistance activities in planning the Mangrove Tourism area. Assistance activities are intended to encourage, assist, and facilitate Village Officials, Tourism Awareness Groups, and the Community in maintaining Mangrove areas and developing Mangrove Tourism so that it becomes a mainstay for Manyar Sidomukti Village. With the assistance activities, Manyarsidomukti Village has a well-planned Mireng River Mangrove Tourism Development Masterplan and can be used as a guideline in carrying out more concrete stages in the future in an effort to make it happen.